Prevalence of antibodies against classical swine fever in two districts of Nepal - Adhikari, Sonu; Gautam, Monica; Shrestha, Riddhi; Ranjit, Eliza; Parajuli, Kanchan; Pandey, Samjhana Kumari Kafle (Archives of Agriculture and Environmental Science, 2023)
This study aimed to investigate the seroprevalence of Classical Swine Fever (CSF), caused by the Classical Swine Fever Virus (CSFV), in the Bhaktapur and Kavrepalanchok districts of Nepal. The primary objective was to determine the prevalence of antibodies against CSFV in the swine population, providing crucial insights for targeted interventions and control strategies. A cross-sectional study was conducted between January and March 2018. The research involved structured questionnaire surveys and blood sample collection from selected farms in the study area. A total of 184 serum samples were collected and subjected to testing using the IDEXX ELISA test kit. The study evaluated seroprevalence by considering variables such as district, sex, age groups, and housing systems. Out of the 184 serum samples collected, 34 were found to be seropositive for CSFV antibodies, resulting in an overall seroprevalence of 18.40%. The study identified significant variations in seroprevalence between different factors, including districts, sexes, age groups, and housing systems. These findings indicate a notable exposure of swine populations in the Bhaktapur and Kavrepalanchok districts to CSFV. This research highlights the considerable risk posed by CSF to the pig populations in the Bhaktapur and Kavrepalanchok districts of Nepal. The identified seroprevalence and variations among different factors emphasize the importance of targeted interventions and control strategies in these regions. The findings serve as a foundation for informed decision-making to mitigate the impact of CSF, safeguard swine health, and protect the livelihoods of those dependent on the swine industry. This study was made possible with the support of the Zoonosis Control Project under the National Animal Science Research Institute, Nepal Agriculture Research Council.